The GRP-MNLF peace agreement a preliminary assessment of its implementation - Muslim, Macapado A. (Philippine Journal of Public Administration, 1999)
This article furnishes a preliminary assessment of the implementation of the 1996 peace accord between the Government of the Republic of the Philippines and the Moro National Liberation Front. Conflict resolution attempts under the Marcos and Aquino administrations are traced together with the main features of the agreement. It also elucidates the status of its implementation and identifies key problems or hindrances. The impact and implications of the achieved progress during its implementation are presented in conclusion.